IMPLEMENTATION OF CONTEXTUAL TEACHING LEARNING (CTL) METHOD TO IMPROVE STUDENT ACTIVITIES AND LEARNING OUTCOMES - Zun Nurani (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
This type of research was classroom action research with the method used was the CTL (Contextual Teaching Learning) method. The subjects of the research were students of class XII IPS SMA Negeri 10 Pekanbaru. The aim of the research was to increase the activities and student learning outcomes carried out by two cycles. Before conducting the learning process, a pre-cycle test was administered with the total score (2390); cycle I (2885), and cycle II (3070). For the average score of pre-cycle test was 68.29, then the first cycle increased to 78.92, and the second cycle increased to 87.71. The results obtained based on the criteria minimum mastery (KKM) 75. This research found that only 8 students (22.86%) fulfilled the minimum criteria while 27 students (77.14%) did not. In the first cycle, the number of students who meet the criteria was 24 (68.57%) with 11 students (31.43%) were incomplete. In the second cycle, 34 students (97.14%) were complete and 02.86% were incomplete. The results based on the high and low pre-cycle score were the highest score of pre-cycle was 85 and the lowest 45; the highest score in cycle I was 95 and the lowest was 80. Based on the range and criteria value with the percentage of pre-cycle was 31.43% (enough); first cycle was very high 37.14 and second cycle was very high criteria 51.43%. The activity of students in each cycle increased ie cycle 1 amounted to 71.43 and cycle II amounted to 85.71. It can be concluded that learning using the CTL (Contextual Teaching and Learning) method can improve student learning outcomes